A Case of Eosinophilic Pustular Folliculitis Associated With Herpes Zoster. (April 2021) - Lee, Jae-Ho; Lee, Soo-Kyung; Kim, Joong-Ho; Kim, Ho-Young; Kim, Myoung-Shin; Lee, Un-Ha
Abstract : Abstract: Patients with eosinophilic pustular folliculitis (EPF), a sterile eosinophilic infiltration of hair follicles, often present with papulopustules that tend to form annular plaques. Histopathologic examination revealed eosinophilic infiltration around the pilosebaceous units and eosinophilic microabscess formation. Although the pathogenesis of EPF is unknown, T-helper type 2 immune responses were suggested to be important based on their stimulating effect on the sebaceous glands. Here, we report the first case of EPF associated with herpes zoster, indicating that herpes zoster and EPF are correlated with T-helper type 2 immune responses.